Pengaruh Kesetaraan Gender, Dukungan Sosial, dan Penghargaan Diri Terhadap Kesejahetraan Subjektif Buruh Bangunan Perempuan Di Desa Sinabun, Kecamatan Sawan, Kabupaten Buleleng - Krisna, Gede; Suwena, Kadek Rai (Jurnal Pendidikan Ekonomi Undiksha, 2025)
Work as a construction laborer in the informal sector is increasingly pursued by women to improve family economic conditions. This study aims to analyze the influence of gender equality, social support, and self-esteem on the subjective well-being of female construction workers in Sinabun Village, Sawan District, Buleleng Regency. This research uses a quantitative approach with multiple linear regression methods. The sample consists of 93 respondents selected using simple random sampling. The results show that gender equality, social support, and self-esteem have a positive and significant impact on the subjective well-being of female construction workers. Among these variables, self-esteem has the most dominant influence, followed by social support and gender equality. Thus, enhancing self-esteem and social support can be effective strategies to improve the subjective well-being of female construction workers.